Characterization and application of biomass gasifier waste material for adsorptive removal of Cr (VI) from aqueous solution. Issue 1 (14th July 2015) - Narayan, Ram; Meena, Rameshwar Prasad; Patel, Amit Kumar; Prajapati, Anuj Kumar; Srivastava, Shalini; Mondal, Monoj Kumar
Abstract : This study was performed to investigate the latent potential of biomass gasifier waste material (BGWM) as an adsorbent for removal of Cr (VI) from aqueous solution. The present work also proposes an alternate use of gasifier refuge BGWM with great economic feasibility. The effects of initial pH, BGWM concentration, Cr(VI) concentration, temperature and contact time were investigated on the removal of Cr (VI) from aqueous solution. The maximum removal of Cr (VI) was found to be 99.67% at optimum condition of initial pH 2, contact time 80 min, initial Cr (VI) concentration 10 mg L −1, adsorbent dose 5 g L −1, agitation speed 120 rpm, and temperature 35°C. The adsorbent was characterised by SEM, EDX, XRD, BET and FTIR analysis to get important information about its effective application for Cr (VI) removal. The BET surface area of 165.287 m 2 g −1 for BGWM was found comparable to that of commercial silica. Batch adsorption experiments showed that pseudo‐second‐order kinetics model and Langmuir isotherm model fitted the adsorption data very well. Thermodynamic parameters revealed the feasibility, spontaneity and endothermic nature of Cr (VI) adsorption onto BGWM. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 95–102, 2016